Gradients of salinity and plant community richness and diversity in two different Mediterranean coastal ecosystems in NW Sardinia - Alfredo Maccioni; Luisa Canopoli; Valeria Cubeddu; Elisabetta Cucca; Simone Dessena; Samuele Morittu; Rossella Filigheddu; Bachisio Mario Padedda; Emmanuele Farris (Biodiversity Data Journal, 2021)
This study aimed to test if differences in soil salinity, plant richness and diversity were significantly affected by habitat, site and distance from the seashore at three sandy and three rocky coastal sites in north-western Sardinia.Each site has been divided into three belts placed at an equal distance of 50 m from the shoreline. We measured soil salinity using a probe and vascular plants richness and diversity using linear transects at all sites. Average soil salinity varied from 0.115 g/l to 0.180 g/l; it was higher in the rocky habitats than in the sandy ones. A total of 21 species were found per transect/site at the rocky sites and 30 species per transect/site at the sandy sites, with an average of Shannon and Weaver's Diversity Index of 1.8 per each belt at each site. These data confirm that, also in the Mediterranean islands, there are coastal gradients of soil salinity from the seashore to inland areas and that also vascular plant richness and diversity are influenced by the distance from the sea. Soil salinity was strongly affected by the type of habitat, being average at the rocky coasts and negligible at the sandy shores. The site effect was not significant for both soil salinity and plant richness and diversity.